Influence of kaolin and red clay on ceramic specimen properties when galvanic sludge is incorporated to encapsulate heavy metals - Brasil, F. M. [UNESP]; Oliveira, D. L.; Melquíades, M. O.; Nobre, F. X.; Balestra, C. E.T.; Ardisson, J. D.; Fabris, J. D.; Santana, G. P.; Ramirez, M. A. [UNESP] (Elsevier, 2024)
This study presented the influence of two types of clay: kaolin (Kao) and red clay (RC) on the chemical and physical properties of ceramic specimens when galvanic sludge (GS) is incorporated to encapsulate heavy metals. Samples were obtained of GS from the industrial district of Manaus – Amazonas State, Brazil, and kaolin (Kao), and red clay (RC) from the Central Amazon. A fourth sample was prepared by mixing GS, Kao, and RC in the ratio 1:1:8 (GS + Kao + RC). This mixture was ground, and ceramic specimens were prepared, and heat treated at 950 °C and 1200 °C for three hours for phase detection, compressive strength, leaching of Fe, Ni and Cr metals and life cycle assessment. Galvanic sludge, Kao, and RC were also, and heat treated to at 950 °C and 1200 °C for three hours, obtaining GS950, GS1200, Kao950, Kao1200, RC950, and RC1200. The samples were submitted to XRF, XRD, Rietveld refinement, Mössbauer spectroscopy, TG/DTG/DSC, and SEM. The results show that the formation of nickel oxide and a spinel solid solution of the type Fe3+{Fe1-y3+,Fe1-x2+,Nix2+,Cry3+}O4 (in which [] = tetrahedral site, {} octahedral site) occurs in GS1200, which is caused by sulfate decomposition to SO2. At 1200 °C, heavy metals are encapsulated, forming other phases such as nickel silicate and hematite. Life cycle assessment was used to verify the sustainability and value of GS in clay for making bricks, and it indicated that the production of ceramics is feasible, reduces the use of clays, and is sustainable.
Keywords: Environmental cleaning; Galvanic sludge; Heavy metal encapsulation; Industrial waste